Scyliorhinus haeckelii, Freckled Catshark - Pollom, R. (2020)
The Freckled Catshark (Scyliorhinus haeckelii) is a small (to 57 cm total length) shark that occurs in the Southwest Atlantic from Bahia, Brazil to northern Argentina. It inhabits the continental shelf and upper slope at depths of 37-402 m, and is often associated with deep-water reefs. This catshark is captured in artisanal and commercial trawl, gillnet, and longline fisheries, and is increasingly retained and sometimes targeted. Fishing pressure is present across its range and is intense in some places, however there are very few data on its catchability and level of interaction with fisheries. Association with deepsea corals indicates that it may have some refuge from trawls over untrawlable areas. Since it is unknown if fishing is causing a population reduction, there is currently inadequate information available to assess the Freckled Catshark beyond Data Deficient.